'You put it all together' – families' evaluation of participating in Family Health Conversations. Issue 1 (9th April 2014) - Benzein, Eva; Olin, Cecilia; Persson, Carina
<x xml:space="preserve">Abstract</x> Aims and objectives To evaluate the Family Health Conversations from the perspective of families living with chronic illness. Methodological design and justification This study has a descriptive qualitative design using semi‐structured evaluative family interviews and conventional content analysis. Ethical issues and approval The study was approved by a Regional Ethical Review Board. Research methods Family Health Conversations were used as an intervention with 14 families living with chronic illness. The outcome measures consisted of evaluative family interviews. Results Families' experiences of the conversations embraced their structure and the interactions with the conversation leaders. All families were satisfied with the conversations, pointing to the importance of having them early in the illness process. The opportunity to talk with someone outside the family was strongly emphasised as promoting well‐being. The experienced significance of the conversations was captured in four categories: creating a whole picture, that is, being given the opportunity to listen to other family members' experiences and fill in potential memory gaps; making the situation manageable, that is, receiving support from other participants in order to handle problems and gain control; facilitating healing, that is, being able to tell their story about what had previously been 'the unspeakable'; and strengthened family cohesion, that is, increased understanding for each other's experiences, thus bringing family members closer together. Study limitations Most families were partners, which could possibly limit transferability of the findings to families constituted by couples. Conclusions Family Health Conversations should be offered as a part of standard care shortly after diagnosis and at various transitions in life.